Study of the Features of Non-Traditional Current Sensors and the Possibilities of their Use in Aircraft - Isgandarov, I.A.; Huseynov, V.S. (Herald of Azerbaijan Engineering Academy, 2024)
The article analyzes the performance characteristics of non-traditional current sensors and the possibilities of their use in aircrafts. The possibilities of using electro-optical voltage sensors based on the Kerr and Pockels effect, magneto-optical current sensors based on the Faraday effect and thermoelectric current sensors in the power supply system of aircraft are considered, and a comparative analysis of the advantages and disadvantages of the non-traditional Rogowski current sensor is carried out. It is shown that magneto-optical current sensors based on the Faraday effect are characterized by large values of measured currents and a wide frequency range. Schemes for constructing traditional current sensors used in aircraft power supply systems are considered, and issues of reliability of protection circuits are analyzed. Options for the development and implementation of non-traditional sensors that make it possible to improve the operational and technical characteristics of various components of the aircraft power supply system are considered in detail. It has been established that the future use of created optoelectronic sensors based on the magneto-optical Faraday effects, electro-optical Pockels and Kerr effects, as well as sensors based on the Rogowski winding for measuring very high currents and voltages in both ground-based and on-board electrical networks can be considered more expedient from a design and technological point of view.